2016
DOI: 10.1186/s12302-016-0095-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles on the standard soil arthropod Folsomia candida (Collembola) and the eukaryote model organism Saccharomyces cerevisiae

Abstract: BackgroundBecause of their antimicrobial properties, silver nanoparticles (AgNPs) have been widely used and have come into contact with the environment. In the present work, an effect of AgNPs on a standard soil organism, Folsomia candida, was studied (in comparison to silver nitrate) focusing on molecular and cellular alterations as ecotoxicological endpoints.ResultsAt the molecular level, an up-regulation of metallothionein-containing protein (MTC) mRNA in AgNP-treated groups indicated toxic heavy metal stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…In addition, in fission yeast, the toxic effects of AgNPs are attributed to the generation of ROS through the release of Ag ions inside the cells internalizing AgNPs 34. Consistent with our results, no increase in ROS production in S. cerevisiae BY4741 treated with 4–100 μg/mL PVP-coated AgNPs,15 and a similar effect of AgNPs on the growth of wild-type and single-gene deletion mutants of S. cerevisiae defective in oxidative stress defense (yap1∆, sod1∆, or sod2∆) have been reported.15 However, Sillapawattana et al observed increased ROS production in S. cerevisiae BY4742 and more prominent growth suppression in ctt1, sod2 , or gsh2 deletion mutants compared to wild type when treated with AgNPs 35. Of note, the discordance of our results with those of Sillapawattana et al may be related to the difference in S. cerevisiae strains and culture conditions.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, in fission yeast, the toxic effects of AgNPs are attributed to the generation of ROS through the release of Ag ions inside the cells internalizing AgNPs 34. Consistent with our results, no increase in ROS production in S. cerevisiae BY4741 treated with 4–100 μg/mL PVP-coated AgNPs,15 and a similar effect of AgNPs on the growth of wild-type and single-gene deletion mutants of S. cerevisiae defective in oxidative stress defense (yap1∆, sod1∆, or sod2∆) have been reported.15 However, Sillapawattana et al observed increased ROS production in S. cerevisiae BY4742 and more prominent growth suppression in ctt1, sod2 , or gsh2 deletion mutants compared to wild type when treated with AgNPs 35. Of note, the discordance of our results with those of Sillapawattana et al may be related to the difference in S. cerevisiae strains and culture conditions.…”
Section: Discussionmentioning
confidence: 85%
“…Glutathione reductase (GR) and GST act in concert with the antioxidant compound GSH and play major roles in mediating the tolerance of a P. aeruginosa strain to various herbicides [78]. Similarly, Folsomia candida exposed to AgNPs displayed decreased levels of GSH and increased GST activity [79]. Exposure of P. putida to environmentally relevant concentrations of AgNPs caused ROS production, glutathione depletion, and inactivation of the antioxidant enzymes superoxide dismutase, catalase, and glutathione reductase [72].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sillapawattana et al (2016) Similar to the evaluations carried out with the microfauna, for the meso and macrofauna, it was observed that there is an effect of the NPs on the abundance and diversity of soils. However, in some cases with contradictory results and again, it is suggested that the adverse effects depend on the type of organisms to be evaluated, methods of application of the NPs, doses and the physical and chemical properties of the soil.…”
Section: Negative Effects Of Nps On Soil Organisms (Mesofauna and Mmentioning
confidence: 52%
“…In agriculture, ENP have been designed for reducing the population of arthropods or pathogens (Dubey & Mailapalli, 2016), increasing the control of diseases or weeds (Duhan et al, 2017), or improving the growth rates of crops with environmental benefits or economic profits (Liu, Zhang, & Lal, 2016). In contrast, it has also been discussed the adverse effects of ENP on soil organ-isms´diversity and abundance Wang, Shu, Zhang, & Youbin, 2017 such as fungus (Duhan et al, 2017), collembola (McKee et al, 2017Sillapawattana, Gruhlke, & Schäffer, 2016;Topuz & van Gestel, 2017), isopods (Malev et al, 2017), annelids (Brami, Glover, Butt, & Lowe, 2017;Jesmer, Velicogna, Schwertfeger, Scroggins, & Princz, 2017;Patricia et al, 2017;Romero-Freire, Lofts, Peinado, & van Gestel, 2017), as well as on the symbiotic association of bacteria and plants (Cao, Fen, Lin, & Wang, 2016). The toxic effects of ENP regarding their bioaccumulation and persistence have also been reported on organisms of different trophic levels (Chae, Kim, & An, 2016).…”
mentioning
confidence: 99%